2014
DOI: 10.1186/1472-6920-14-186
|View full text |Cite
|
Sign up to set email alerts
|

The use of clinical guidelines highlights ongoing educational gaps in physicians’ knowledge and decision making related to diabetes

Abstract: BackgroundClinical guidelines for type 2 diabetes are a resource for providers to manage their patients and may help highlight specific areas in need of further education and training. We sought to determine how often guidelines are used and the relationship to physicians’ diabetes-related knowledge and decision making.MethodsExisting users of electronic clinical support tools were invited to complete an online questionnaire. A knowledge score was calculated for five questions related to prevention of diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Other studies suggest that physicians may disregard scientific data and/or guidelines when prescribing anti‐hyperglycaemic drugs. In a survey, among 383 practicing physicians treating patients with diabetes in the USA, close to 50% answered that they were unfamiliar with the American Diabetes Association (ADA)/European Association for the Study of Diabetes (EASD) and American Association of Clinical Endocrinologists (AACE) guidelines or that they did not rely on these guidelines . Among the same physicians, diabetes‐related knowledge and the quality of clinical decision‐making were lower compared to those physicians integrating the diabetes guidelines in their clinical practice .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that physicians may disregard scientific data and/or guidelines when prescribing anti‐hyperglycaemic drugs. In a survey, among 383 practicing physicians treating patients with diabetes in the USA, close to 50% answered that they were unfamiliar with the American Diabetes Association (ADA)/European Association for the Study of Diabetes (EASD) and American Association of Clinical Endocrinologists (AACE) guidelines or that they did not rely on these guidelines . Among the same physicians, diabetes‐related knowledge and the quality of clinical decision‐making were lower compared to those physicians integrating the diabetes guidelines in their clinical practice .…”
Section: Discussionmentioning
confidence: 99%
“…The resulting milieu in which the participants received care was neither conducive to positive patient‐provider relationships nor individuals' efforts to successfully self‐manage T2DM. In addition, despite extensive research articulating the attributes and skills that best support and empower patients, there is little evidence that healthcare providers are universally competent in demonstrating, performing, or integrating these behaviors into practice (Corriere, Minang, Sisson, Brancati, & Kalyani, ; Hudon, Lambert, & Almirall, ).…”
Section: Discussionmentioning
confidence: 99%
“…Corriere et al. () noted that ADA guidelines are a valuable resource for PCPs in the management of patients with diabetes. According to Tunceli et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study demonstrated how frequently guidelines were used by PCPs and the relationship to PCPs diabetes‐related knowledge, attitude, and decision‐making. The same study showed 53% of PCPs using guidelines daily had better results when compared to nonguidelines users (Corriere et al., ).…”
Section: Review Of the Literaturementioning
confidence: 93%
See 1 more Smart Citation